Biomechanical analysis of specific motor impairments contributing to early functional decline in adults living with HIV-1 infection : a sub-study to the Cape Winelands HAART to HEART (Prevalence)/EndoAfrica study - Berner, Karina (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.